Farmer Participatory Evaluation of Groundnut Varieties - Satish Kumar, S.P. Singh, G.D. (Indian Journal of Extension Education, 2022)
Groundnut is a major oilseed crop of Orissa, which accounts for 57% of total oil seed production of the state of identifying. The total area under groundnut in the state was 0.90 lakh ha of which 0.52 lakh ha was grown during rabi season. The rabi season sowing starts from October and ends in February depending on the time of harvesting of rice crop. The rabi groundnut is grown mostly in coastal districts where rice based cropping system is the most predominant system and groundnut is grown entirely on residual soil moisture without irrigation. Growing groundnut, a legume, in the rice based cropping system sustains crop production and even improves soil health provides better nutritional and financial security. The major constraint for rabi groundnut cultivation was lack of awareness on improved varieties and non-availability of quality seed. Farmers grow traditional varieties. Hence, the present study was conducted with the following objectives the suitable groundnut variety for Coastal Orissa for rabi season-1 and to demonstrate the potential of seed storage method, improved agro-techniques and other production techniques suitable for different agroclimatic zones in the country. But there are wide gaps between the available technologies and their adoption.